Marketing Mix Factors Influencing Consumer Purchase Decisions of Eco-Friendly Detergent - Muhammad Rizqi Yudhistira; Krismi Budi Sienatra (LPPM dan Fakultas Ekonomi dan Bisnis Universitas Kahuripan Kediri, 2026)
Currently, MSMEs have begun to expand into environmentally friendly products, for example, environmentally friendly detergents that emphasize green products. As a consumer product used daily, detergent purchasing decisions are influenced by various factors, such as price, promotion, and product quality. MSMEs must fulfill these three things to attract customer interest and thus influence their purchasing decisions. This study aims to determine the effect of price, promotion, and product quality on purchasing decisions of Ray Shop consumers. This study uses a quantitative research type. The data collection method used is a questionnaire. The number of samples used is 50 respondents. The data analysis technique used by researchers in this study is multiple linear regression analysis. The results of the study indicate that there is an influence of price, promotion, and product quality on purchasing decisions of eco-friendly detergents.